2003
DOI: 10.1385/nmm:3:1:53
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 Mutation Sensitizes Oligodendrocytes to Glutamate and Amyloid Toxicities, and Exacerbates White Matter Damage and Memory Impairment in Mice

Abstract: Damage to white matter occurs in the brains of patients with Alzheimer s disease (AD), but it is not known if and how oligodendrocytes are affected in AD, nor whether white matter alterations contribute to the cognitive dysfunction in this disease. Mutations in the gene encoding presenilin-1 (PS1) cause some cases of early-onset inherited AD. These mutations may promote neuronal degeneration by increasing the production of neurotoxic forms of amyloid beta-peptide and by perturbing cellular calcium homeostasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 44 publications
1
48
1
Order By: Relevance
“…We hypothesized that myelin breakdown in vulnerable late-myelinating regions ( Figure 1B, D) releases oligodendrocyte-and myelin-associated iron [19,21,28,38,39], thus promoting Aβ oligomerization, its associated toxicity, and deposition of oligomerized Aβ and iron in neuritic plaques [7,28,[40][41][42][43] (Figure 1A, C). This hypothesis has been supported in transgenic mouse models that demonstrated increased vulnerability of oligodendrocytes to toxicity [44], agerelated white matter volume reductions [45], and age-related iron deposition in amyloid plaques [42]. Human studies have likewise confirmed age-related myelin breakdown that is exacerbated in healthy APOE e4 carriers and AD subjects [7,43] and age-related increases in brain iron [21] that are exacerbated in AD subjects [28].…”
Section: Methods Results and Discussionmentioning
confidence: 82%
“…We hypothesized that myelin breakdown in vulnerable late-myelinating regions ( Figure 1B, D) releases oligodendrocyte-and myelin-associated iron [19,21,28,38,39], thus promoting Aβ oligomerization, its associated toxicity, and deposition of oligomerized Aβ and iron in neuritic plaques [7,28,[40][41][42][43] (Figure 1A, C). This hypothesis has been supported in transgenic mouse models that demonstrated increased vulnerability of oligodendrocytes to toxicity [44], agerelated white matter volume reductions [45], and age-related iron deposition in amyloid plaques [42]. Human studies have likewise confirmed age-related myelin breakdown that is exacerbated in healthy APOE e4 carriers and AD subjects [7,43] and age-related increases in brain iron [21] that are exacerbated in AD subjects [28].…”
Section: Methods Results and Discussionmentioning
confidence: 82%
“…The coexpression of PSEN1 with known myelin-associated genes in both studies, and its high connectivity in the AD study, suggests that PSEN1 may play a role in oligodendrocyte dysfunction or demyelination in AD. Pak et al (2003) found that oligodendrocytes in PSEN1 mutant knock-in mice were more prone to damage by demyelinating agents and death by glutamate and ␤-amyloid toxicity. These results fit the hypothesis that AD progression follows a trajectory opposite in time to cortical myelination (Braak and Braak, 1996), because the later-made oligodendrocytes progressively myelinate a greater number of axonal segments, making them more vulnerable to AD risk factors such as head injury and high cholesterol (Bartzokis, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…38,39 This familial AD mutation has been shown to hypersensitize oligodendrocytes to various insults associated with AD, including A␤ peptides. 40 Hence, it is possible that the A␤-induced changes in oligodendrocyte marker expression and myelin structure are at least partially mediated through oligodendrocyte-expressed PS1 M146V . Isolation of each potential genetic player in single and double-transgenic AD mice, as well as generation of conditional transgenics with oligodendrocyte-specific expression profiles, will help to differentiate "oligocentric" mechanisms from pathogenic signals indirectly derived from other A␤-assaulted cell types.…”
Section: Discussionmentioning
confidence: 99%